2015
DOI: 10.1007/978-3-662-48057-1_11
|View full text |Cite
|
Sign up to set email alerts
|

A Circuit Complexity Approach to Transductions

Abstract: We investigate the deterministic rational transductions computable by constant-depth, polysize circuits. To this end, we first propose a framework of independent interest to express functions of variable output length using circuits, and argue for its pertinence. We then provide a general characterization of the set of transductions realizable by such circuits, relying on a notion of continuity. We deduce that it is decidable whether a transduction is definable in AC 0 and, assuming a well-established conjectu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In [18], the authors use the term "preserving" in the more general context of functions from monoids to monoids. In our study, we focus on word to word functions, in which the natural topological context provides a solid basis for the use of "continuous," as used in [16,5].…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…In [18], the authors use the term "preserving" in the more general context of functions from monoids to monoids. In our study, we focus on word to word functions, in which the natural topological context provides a solid basis for the use of "continuous," as used in [16,5].…”
Section: Preliminariesmentioning
confidence: 99%
“…This pervasive interaction naturally suggests lifting this study to the functional level, hence to rational functions. This was started in [5], where it was shown that a subsequential (i.e., inputdeterministic) transducer computes an AC 0 function iff it preserves the regular languages of AC 0 by inverse image. Buoyed by this clean, semantic characterization, we wish to further investigate this latter property for different classes: say that a function f : A * → B * is V-continuous, for a class of languages V, if for every language L ⊆ B * of V, the language f −1 (L) is also a language of V. Our main focus will be on deciding V-continuity for rational functions; before listing our main results, we emphasize two additional motivations.…”
Section: Introductionmentioning
confidence: 99%
“…For word functions, a recent work (Cadilhac et al 2015) shows that it is decidable whether a deterministic rational transduction is definable in the circuit class AC 0 (resp. ACC 0 ), also using an algebraic approach.…”
Section: Related Workmentioning
confidence: 99%
“…In contrast to considering restrictions of the transition congruence of the underlying automata of transducers, a different way of defining subclasses of rational transductions, taking into account the outputs, has been proposed in [CKLP15] and [CCP17]. It is based on the natural notion of continuity, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In [CKLP15], the authors were able to effectively characterize sequential transductions definable by AC 0 circuits. In [CCP17] the authors show how to decide if a transduction is continuous with respect to many usual varieties and they also compare the two notions of continuity and realizability.…”
Section: Introductionmentioning
confidence: 99%